Editorial Foreword - Ab Gani, Muhamad Abdul Aziz; Ramli, Ishak; Yahaya, Mohammad Hafiz; Taharuddin, Nurul Shima; Md Nazri, Haslinda; Rosman, Muhammad Redza BIN; Nazrin, Nizar (Idealogy Journal; Vol 5 No 2 (2020): Idealogy Journal (September 2020)DO - 10.24191/idealogy.v5i2.282, 2020)
We are very pleased that IDEALOGY JOURNAL is presenting its 5th volume and 2nd issue. We are also very excited that the journal has been attracting papers from a variety of advanced and emerging countries such as Indonesia, Pakistan, Saudi Arabia, Bangladesh, etc. The variety of submissions from such countries will help the aimed global initiatives of the journal.